Virtual Tour Sebagai Alternatif Berwisata Di Masa Pandemi Covid-19 (Studi Pada Pelaku Wisata di Yogyakarta) - Ema Rahmawati; Ndaru Prasastono; Andi Susanto; Moko Dwiarto Sudiro (Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2022)
This study discusses how virtual tours can be an alternative to traveling online during the covid 19 pandemic. By using a qualitative descriptive method, the author wants to describe how many tourism actors use virtual tours as tourism products that promise to be sold during the covid 19 pandemic. By presenting pictures and videos along with digital tour guides, they are able to make tourists feel curious so that they are interested in buying these products and enjoying them only with laptops, computers (PCs), smart wires and internet networks and can be accessed anywhere. The author's observations from 158 travel agencies in Yogyakarta that are members of ASITA are only about 10% or 15 travel agencies that sell tourism products/tour packages virtually, while tour guides who are members of the DIY Indonesian Guides Association (HPI) are only around 5% or 25. only people involved in virtual tour activities. The lack of tourism actors who carry out virtual tour activities is due to the lack of availability of virtual tour supporting equipment, inadequate human resources, difficulties in marketing tourism products/tour packages, and there are still many consumers who want to buy tourism products/tour packages directly.Keywords: Virtual Tour, Tour Actors, Tour Packages